ANALISIS METODE HEURISTIK LINE BALANCING UNTUK OPTIMASI KESEIMBANGAN LINTASAN PADA PROSES SEWING PRODUKSI SARUNG TANGAN GOLF - Hidayat Al Ma'ruf; Suseno Suseno (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The golf glove sewing production line at PT XYZ experienced line imbalance, as indicated by differences in workstation cycle times that caused bottlenecks, high idle time, and low line efficiency. This study aimed to improve production line performance by applying three heuristic line balancing methods: Ranked Positional Weight (RPW), Largest Candidate Rule (LCR), and Region Approach (RA). Line performance was evaluated using line efficiency, balance delay, idle time, smoothness index, and the number of workstations. The initial production line consisted of 12 workstations with a line efficiency of 67.63%, a balance delay of 32.37%, a smoothness index of 50.78, and a total idle time of 159.81 seconds.